RETRACTED: Qualitative indicators of meat productivity of Zaanen goats when using the probiotic bacillus Amyloliquefaciens VKPM V-11475 - Molyanova Galina; Statenko Bogdan; Vinokurova Alisa (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001